Limited knowledge and fear of transmission sustain HIV-related stigma among healthcare workers in Bireuen, Indonesia - Abd Hadi; Asnawi Abdullah; Hermansyah Hermansyah; Maidar Maidar; Basri Aramico (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: HIV/AIDS cases in Aceh reached 1,641 in 2024, with 176 cases in Bireuen and 11 patients at Cot Ie Jue Community Health Center. Stigma and discriminatory attitudes among healthcare workers (HCWs) pose a major challenges for people living with HIV/AIDS, affecting service quality. Purpose: To explore the causes, manifestations, and perceived consequences of HIV-related stigma among healthcare workers at Cot Ie Jue Community Health Center, Bireuen, Indonesia. Method: Qualitative research was employed. Data were collected through in-depth interviews and focus group discussions (FGDs) with 25 informants (doctors, nurses, midwives, etc.) in July 2025, analyzed through reduction, display, and conclusion drawing. Results: HCW stigma is driven by a lack of knowledge and misconceptions about HIV transmission and its impact. This stigma causes anxiety and discomfort in providing care, leading to discriminatory attitudes, avoidance, and low empathy. Patients’ understanding of the importance of ARV therapy and side effects also remains a challenge. Conclusion: Continuous education and training on HIV/AIDS (transmission, prevention, treatment, care), along with effective communication training, are crucial to enhance HCWs' knowledge and ensure empathetic, stigma-free, and supportive interactions with patients.